2019
DOI: 10.1002/ppap.201900019
|View full text |Cite
|
Sign up to set email alerts
|

Validation of etching model of polypropylene layers exposed to argon plasmas

Abstract: Thin layers of polypropylene (PP) have been treated by argon low‐temperature plasmas in an inductively coupled plasma setup. The etched thickness of PP was monitored in situ by means of single‐wavelength ellipsometry. The ellipsometric model of the polymer surface exposed to plasma consists of a UV‐modified layer, a dense amorphous carbon layer because of ion bombardment, and an effective medium approximation layer, which accounts for moderate surface roughness. The etching behavior has been compared to a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Such initial surface chemistry modification of the PS followed by a constant slow‐paced plasma etching of polymer thin films was also observed and discussed by Rastogi et al. [ 42 ] for PS as well as by the group of von Keudell [ 47,48 ] for other polymers. Possible explanations for this behavior include UV radiation‐induced breaking of CC and CH bonds, cross‐linking, and surface graphitization, which result in the formation of a passivation layer which then retards the etching of PS.…”
Section: Resultsmentioning
confidence: 61%
“…Such initial surface chemistry modification of the PS followed by a constant slow‐paced plasma etching of polymer thin films was also observed and discussed by Rastogi et al. [ 42 ] for PS as well as by the group of von Keudell [ 47,48 ] for other polymers. Possible explanations for this behavior include UV radiation‐induced breaking of CC and CH bonds, cross‐linking, and surface graphitization, which result in the formation of a passivation layer which then retards the etching of PS.…”
Section: Resultsmentioning
confidence: 61%
“…It was found that the depth of the modified layer was 40-50 nm in this case. The authors compared the experimental and theoretical data on determination of the depth of the modified layer for a polypropylene (PP) film treated by inductively coupled RF argon plasma [9]. Experimental data, obtained using ellipsometry, ion bombardment etching, and exposure to vacuum ultraviolet radiation, were in good agreement with the simulation results.…”
Section: Introductionmentioning
confidence: 81%
“…It is currently believed that the depth of a modified layer of polymers, treated by various kinds of discharges, is in the range from several nanometers to ≤1-2 µm. However, we know only a few works devoted to the experimental determination of the depth of the modified layer after plasma treatment of polymers [7][8][9], although this parameter is very important for understanding the mechanism of plasma action on the surface of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this model was validated in an inductively coupled plasma setup by ellipsometry. [15] Thus, the separation of different plasma-related effects can lead to a deeper understanding of the overall plasma process and afterward be transferred to different and more complex plasma setups.…”
Section: Introductionmentioning
confidence: 99%